Teaching and practical guidelines in pulp therapy in primary teeth in Colombia – South America (2014)
Objective To describe the teaching practical guidelines in pulp therapy for primary teeth in Colombian dental schools, based on Primosch et al . survey (1997). Methods A 27‐question survey was sent to 31 dental schools. A total of 68 surveys were obtained for analysis of the results, in which pediatric dentists answered 48 surveys, 11 surveys by general practitioners, and 9 were answered but were not identified in any of these groups. Results Indirect pulp treatment (IPT ) is taught by pediatric dentists (83%) and general practitioners (90%). Calcium hydroxide and glass ionomer were the preferred materials in this treatment. Pulpotomy is the most commonly procedure used. There was no different percentage in the use of medicaments: cresatin, glutaraldehyde, calcium hydroxide, formocresol. Pulpectomy is taught by general practitioners (73%) and pediatric dentists (96%). The preferred filler material, used by general practitioners (73%) and pediatric dentists (94%), was zinc oxide and eugenol. Conclusions There is a discrepancy in the choice of treatment and medications for pulp therapy primary teeth between general practitioners and pediatric dentists. The recommendations given in American Academy of Pediatric Dentistry (AAPD ) guidelines 2012 for pulp therapy in primary and young permanent teeth are being followed in the majority instances.